Recent advances in heat shock proteins in cancer diagnosis, prognosis, metabolism and treatment - Yang, Shuxian; Xiao, Haiyan; Cao, Li (Biomedicine & pharmacotherapy, 2021)
Heat shock proteins (HSPs) are a group of proteins, also known as molecular chaperones, which participate in protein folding and maturation in response to stresses or high temperature. According to their molecular weights, mammalian HSPs are classified into HSP27, HSP40, HSP60, HSP70, HSP90, and large HSPs. Previous studies have revealed that HSPs play important roles in oncogenesis and malignant progression because they can modulate all six hallmark traits of cancer. Because of this, HSPs have been propelled into the spotlight as biomarkers for cancer diagnosis and prognosis, as well as an exciting anticancer drug target. However, the relationship between the expression level of HSPs and their activity and cancer diagnosis, prognosis, metabolism and treatment is not clear and has not been completely established. Herein, this review summarizes and discusses recent advances and perspectives in major HSPs as biomarkers for cancer diagnosis, as regulators for cancer metabolism or as therapeutic targets for cancer therapy, which may provide new directions to improve the accuracy of cancer diagnosis and develop more effective and safer anticancer therapeutics. [Display omitted] •HSF-1 and HSPs can be used as biomarkers for cancer diagnosis and prognosis.•HSPs, particularly HSP70 and HSP90, participate in and regulate cancer metabolism.•Two approaches are employed to target HSPs for cancer therapy, including HSP inhibitors and HSP-based immunotherapies.•The combination of the HSP inhibitors with conventional therapies will help improve the therapeutic outcome.•HSP-based targeting or immunotherapy will remain a major focus in the field of cancer therapy.